2020
DOI: 10.1021/acsanm.0c02358
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Triggered Self-Assembled Egg White Protein-Coated Gold Nanoclusters for Selective Fluorescent Detection of Fe3+, NO2, and Cysteine

Abstract: Herein, we present a simple and economical synthesis for the first multianalyte probe able to selectively quantify the concentrations of Fe3+, NO2 –, and cysteine. It comprises H+-triggered self-assembled gold nanoclusters (AuNCs@EW/H+, AuEHs), showing enhanced red fluorescence at 640 nm. The AuEH is a good fluorescent nanosensor for Fe3+ and NO2 – with detection limits of 1.40 and 2.82 nM, respectively. Iron detection, through fluorescence quenching, occurs because of nanocluster aggregation elicited by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 59 publications
(80 reference statements)
0
16
0
Order By: Relevance
“…prepared H + ‐triggered self‐assembled Au NCs (AuEH) based on egg white‐functionalized Au NCs. [122] These AuEH can be used as probes for the detection of multianalytes. One of the analytes is Fe 3+ that can trigger the aggregation of AuEH by the complexation of Fe 3+ with amino acids on the surface of AuEH.…”
Section: Biosensing Strategiesmentioning
confidence: 99%
“…prepared H + ‐triggered self‐assembled Au NCs (AuEH) based on egg white‐functionalized Au NCs. [122] These AuEH can be used as probes for the detection of multianalytes. One of the analytes is Fe 3+ that can trigger the aggregation of AuEH by the complexation of Fe 3+ with amino acids on the surface of AuEH.…”
Section: Biosensing Strategiesmentioning
confidence: 99%
“…Copyright 2020 Elsevier B.V. (d) Synthesis of the AuEH and a profile of its sensing behavior toward Fe 3+ , NO 2 – , and Cys. Reproduced with permission from ref . Copyright 2020 American Chemical Society.…”
Section: Metal Nanoclusters Applied In Biologymentioning
confidence: 99%
“…On the contrary, the Cu 2+ ions can highly interact with the surface ligand and generate large-size Cu 2+ –Au NCs, which induces aggregation and results in fluorescence quenching. Li and co-workers synthesized egg white protein-protected Au NCs, and its fluorescent performance is selectively sensitive to Fe 3+ and NO 2 – with detection limits of 1.40 and 2.82 nM, respectively . They found that the fluorescence quenching by iron is due to the interaction between Fe 3+ and the carboxyl and amino group of the surface protein, inducing the aggregation of Au NCs to form lager particles, Figure b .…”
Section: Metal Nanoclusters Applied In Biologymentioning
confidence: 99%
See 2 more Smart Citations